Multilayer composite current collector, pole piece and lithium ion battery
By introducing an adhesion enhancement layer between the polymer substrate layer and the conductive metal layer, a multi-layer composite fluid is formed, and the problem of insufficient binding force and electrolyte resistance of each layer in the prior art is solved, thereby achieving efficient lithium The preparation of ion battery current collector improves the safety and energy density of the battery.
Patent Information
- Application Number
- CN202310943630.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing new composite collector preparation technology, there are problems such as insufficient bonding force and electrolyte resistance of each layer, easy peeling of the metal layer, and difficult processing during the coating of the positive and negative electrode slurry.
A multi-layer composite fluid collector structure is adopted, which includes an adhesion enhancement layer between the polymer substrate layer and the conductive metal layer. The adhesion enhancement layer is formed by vapor deposition, evaporation coating method or coating method to increase the bonding force of each layer. and electrolyte resistance.
A multi-layer composite fluid with high binding force, strong electrolyte resistance, high tensile strength and high processing convenience is achieved, reducing the possibility of metal layer peeling and improving the safety and energy density of lithium-ion batteries.
Smart Images

Figure BDA0004366464000000131 
Figure BDA0004366464000000141
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of current collectors, and in particular to a multilayer composite current collector, a pole piece containing the same, and a lithium-ion battery. Background Art
[0002] In the lithium battery industry, the current collector is a key auxiliary material for lithium-ion batteries. It not only acts as a carrier for the positive and negative active materials, but also as a matrix for the collection and conduction of positive and negative electrons. Its function is to collect the current generated by the active materials of the battery to generate a larger output current. This realizes the process of converting chemical energy into electrical energy. Therefore, the ideal current collector often needs to have comprehensive properties such as high conductivity, good stability, good mechanical strength, and low cost. The current mainstream positive and negative current collectors are aluminum foil and copper foil.
[0003] With the rapid development of the electric vehicle market and the consumer electronics market, there are higher requirements for the range of electric vehicles and the standby time of consumer electronic devices, so the requirements for the energy density of lithium batteries are also getting higher and higher. If the weight and thickness of the positive and negative electrode materials can be kept unchanged, reducing the weight and thickness of the current collector is an effective way to increase the energy density of the battery.
[0004] Lithium batteries with metal foil current collectors used in traditional technologies are prone to burrs when subjected to sudden abnormal conditions such as external extrusion, collision or needle puncture, which can puncture the separator between the positive and negative electrodes, causing a short circuit between the positive and negative electrodes, generating a large amount of heat, causing the overall temperature of the battery to rise, and a series of chain reactions such as thermal decomposition of the electrolyte, separator, and positive and negative electrode materials, which can easily cause serious hazards such as fire and explosion. Therefore, in order to improve the safety of lithium batteries and increase the energy density of lithium batteries, a new type of thin film composite current collector is being studied. Due to its sandwich structure of resin and metal, it reduces the amount of metal used, and therefore also reduces the possibility of the above-mentioned short circuit, so it plays a very important role.
[0005] Patent document CN211957791U discloses a current collector with a composite structure, which uses a porous structure to increase the contact area of the coating surface. Although it can improve the current density and rate performance of the battery, the bonding strength and corrosion resistance between the layers of the composite structure are insufficient, which may also cause safety problems.
[0006] Patent document CN109088045A discloses a method for preparing a high energy density lithium-ion battery, wherein the current collector is obtained by sputtering copper metal and aluminum metal onto a polymer fiber textile fabric using magnetron sputtering technology to obtain porous copper foil and porous aluminum foil. However, the non-woven fabric is soft in texture and lacks its own rigidity. In the subsequent battery manufacturing process, this problem will seriously affect the coating operation of the positive and negative electrode slurries. In addition, the processing time and processing cost of magnetron sputtering are very high, making it difficult to achieve mass production and unable to cope with the huge market demand. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the current new composite current collector preparation technology, such as insufficient bonding strength and electrolyte resistance of each layer, easy peeling of the metal layer, and processing difficulties when using the composite current collector for coating the positive and negative electrode slurries.
[0008] In order to solve the above problems, the present invention provides a multilayer composite current collector, which comprises a polymer substrate layer, and a conductive metal layer arranged on both sides of the polymer substrate layer, wherein an adhesion enhancement layer is provided between the polymer substrate layer and the conductive metal layer, and the tensile strength of the composite current collector is above 150 MPa in the MD direction and above 150 MPa in the TD direction. According to the present invention, it is possible to provide a multilayer composite current collector with strong bonding strength and electrolyte resistance of each layer, high overall tensile strength, high processing convenience, and a metal layer that is not easy to peel off, as well as a pole piece and a lithium-ion battery comprising the same.
[0009] <Adhesion Enhancement Layer>
[0010] The bonding force between the polymer substrate layer and the conductive metal layer has a very important influence on the application of the composite current collector. If the conductive metal layer peels off, it is easy to cause the positive and negative electrode materials to fall off, causing serious defects in the battery. By introducing an adhesion enhancement layer between the polymer substrate layer and the conductive metal layer, the bonding force between the two can be improved. On the one hand, the heat resistance and electrolyte resistance of the substrate are improved, while at the same time, the defective rate of the composite current collector during processing is improved and its electrolyte resistance stability is improved, thereby increasing the overall cycle life of the battery.
[0011] As a method for forming the adhesion enhancing layer, a primer layer can be added on both sides of the polymer substrate layer by vapor deposition, evaporation coating or coating as the adhesion enhancing layer. Furthermore, in order to increase the adhesion between the polymer substrate layer and the conductive metal layer and improve the electrolyte resistance of the composite current collector, it is preferred that the surface of the polymer substrate layer is first treated with plasma, corona or the like before forming the adhesion enhancing layer.
[0012] The material of the adhesion enhancing layer includes metals, metal oxides or alloys such as copper alloy, metal nickel, nickel alloy, titanium, titanium alloy, aluminum oxide, and aluminum alloy. The adhesion enhancing layer can be formed on both sides of the polymer substrate layer by vapor deposition or evaporation coating.
[0013] In addition, as the material of the adhesion enhancing layer, one or more of polyurethane resin, modified polyolefin resin, epoxy resin, unsaturated polyester resin, acrylic resin or fluororesin can also be listed, and the adhesion enhancing layer can be formed on both sides of the polymer substrate layer by coating.
[0014] Among them, from the viewpoint of improving the adhesion with the polymer substrate layer and the conductive metal layer, it is preferred that the resin-based adhesion enhancing layer contains one or more functional groups selected from -COOH, -Ar-OH, -OH, -Cl, -NHCO-, -NH2, -SH, -Si-OH, -CHO, -OC(=O)-O-, -CO-O-. The above functional groups can be analyzed and judged by FTIR or XPS. Considering the convenience of the analysis method, it is preferred to use FTIR for analysis and judgment. The detected peak position of each functional group may fluctuate due to the influence of the instrument model, the connected group, etc., and the position that can be judged by an experienced person shall prevail.
[0015] Furthermore, in order to improve the adhesion between the substrate and the metal layer, the resin matrix of the adhesion enhancing layer is preferably polyurethane resin and / or modified polyolefin resin. The mechanism is that polyurethane resin and modified polyolefin resin have good compatibility with most polymer substrates, and the above-mentioned various functional groups have good compatibility with conductive metals, so the adhesion between the polymer substrate and the conductive metal layer can be improved.
[0016] Considering the cost control, processing convenience and better bonding strength of the lithium battery industry, it is preferred that the adhesion enhancement layer is realized on both sides of the polymer substrate layer by coating. The coating method can include one or more of roll coating, extrusion coating, blade coating, gravure coating, etc.
[0017] The thickness of the adhesion enhancement layer is 10 nanometers to 1000 nanometers. Considering that the thinner the overall thickness of the composite current collector is, the thinner the overall thickness of the lithium battery will be, and the smaller the battery volume will be, the thickness of the adhesion enhancement layer is preferably 20 to 500 nanometers.
[0018] <Polymer Base Material Layer>
[0019] As for the polymer substrate layer of the present invention, the material thereof is not particularly limited as long as it is a conventional polymer material that can be used for the current collector substrate. However, a large amount of heat may be generated during the current collector processing, so the higher the heat resistance temperature of the polymer substrate layer and the smaller the change in thermal shrinkage, the better the heat resistance of the composite current collector, and the probability of the conductive metal layer breaking during processing will be reduced. Therefore, considering the heat resistance during processing and the electrolyte resistance required in the battery, the material of the polymer substrate layer is preferably one or more of polyester, polypropylene, polyimide, polyphenylene sulfide, polyamide, polyvinyl chloride, polyetheretherketone or polyether.
[0020] For the polymer substrate layer, biaxial stretching can improve the heat resistance, electrolyte resistance, mechanical properties and uniformity of various properties of the film, reduce thermal shrinkage, and help improve the adhesion between the conductive metal layer and the conductive metal layer, so that the conductive metal layer can be more firmly combined with the polymer substrate layer. Therefore, the polymer substrate layer is preferably a biaxially stretched material. It is further preferred that the material of the polymer substrate layer is one or more of a biaxially stretched polyethylene terephthalate film, a biaxially stretched polyphenylene sulfide film or a polypropylene film.
[0021] The polymer substrate layer can be processed by evaporation, electroplating or sputtering to make it conductive, so as to meet the use requirements of the lithium battery current collector. A large amount of heat may be generated during the processing. Due to the characteristics of the polymer material, if the use temperature exceeds the glass transition temperature of the material itself, the polymer material will change from a hard and brittle glass state to a soft, rubber-like, highly elastic state, so the mechanical properties of the material itself will be attenuated to a certain extent. The composite current collector for the positive electrode is mostly processed by evaporation, and the evaporation process is more likely to generate heat and cause the attenuation of the mechanical properties of the polymer substrate. In the later processing of the pole piece, the mechanical properties of the polymer substrate are required to be better, so that the yield of the pole piece in the coating, drying rolling and battery winding processes will be higher (specifically, the higher the tensile strength, the more conducive to processing). Therefore, the polymer substrate layer for the positive composite current collector in the present invention preferably has a tensile strength of 250Mpa or more in the MD direction, and more preferably 300MPa or more. The tensile strength in the TD direction is preferably 200Mpa or more, and more preferably 220MPa or more. The composite current collector for the negative electrode is mostly processed by electroplating, which has little effect on the mechanical properties of the material itself. Therefore, the polymer substrate layer of the composite current collector for the negative electrode in the present invention preferably has a tensile strength of 150 MPa or more in the MD direction and 200 MPa or more in the TD direction.
[0022] The thickness of the polymer substrate layer is 1 micrometer to 8 micrometers. Considering the processability of the multi-layer composite current collector and the processability of the battery, the thickness of the polymer substrate is preferably 2 micrometers to 6 micrometers.
[0023] <Conductive Metal Layer>
[0024] The material of the conductive metal layer can be one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver and silver alloy. Considering the positive and negative electrode potentials in lithium batteries, as well as cost and mass production, the conductive metal layer of the composite current collector for the positive electrode is preferably aluminum, and the negative electrode is preferably copper. The higher the purity of the conductive metal layer, the less the conductive metal layer and the polymer substrate layer are affected by the electrolyte, etc., and the higher the comprehensive performance of the multilayer film. Therefore, the purity of the metal layer is preferably ≥99.8% in the present invention.
[0025] The thickness of the conductive metal layer is 0.5 micrometers to 2 micrometers. Considering the conductivity of the current collector and the use as a carrier of positive and negative electrode active materials, the thickness of the metal layer is preferably 0.6 micrometers to 1.5 micrometers.
[0026] The conductive metal layer can be prepared on both sides of the polymer substrate layer by at least one or more of vacuum sputtering, evaporation coating, chemical coating, metal foil lamination, electrochemical deposition, chemical vapor deposition, and physical vapor deposition. The chemical electrochemical deposition includes chemical plating, water electroplating, laser plating, etc. In the case of multiple preparation methods, the processing can be performed sequentially or simultaneously by multiple methods. In view of production efficiency and improving the purity of the conductive metal layer, it is preferred that a conductive metal layer is provided on the polymer substrate layer with an adhesion enhancing layer by evaporation coating or electrochemical deposition.
[0027] <Multilayer Composite Current Collector>
[0028] When the active material is coated on the electrode, the current collector with high tensile strength has a stronger supporting ability for the current collector and is less affected by rolling, which is beneficial to improving the yield rate of the electrode and the battery. Therefore, in the present invention, the tensile strength of the multilayer composite current collector in the MD direction is preferably set to be above 150 MPa, and that in the TD direction is above 150 MPa.
[0029] Since the main function of the current collector is to conduct electricity, the better the conductivity, the faster the charge and discharge speed of the battery. Therefore, the sheet resistance of the multilayer composite current collector is preferably 50 milliohms or less. For the current collector of the positive electrode, the sheet resistance of the conductive metal layer is preferably 40 milliohms or less. For the current collector of the negative electrode, the sheet resistance of the conductive metal layer is preferably 30 milliohms or less.
[0030] The multilayer composite current collector has a shedding rate of less than 2% after being treated with an electrolyte solution at 80°C for 3 days. The shedding rate of the conductive metal layer can be determined by a test method of peeling using a high-speed stripping machine. The above method is only for the convenience of explaining the results of the present invention, and is not used as the only criterion for specifying or determining the results, and does not constitute a limitation on the present invention.
[0031] In the prior art, during the electrolyte treatment process of the current collector, the electrolyte will penetrate into the interior through the edge of the multilayer film or the defective parts in the conductive metal layer, resulting in reduced adhesion between the conductive metal layer and the polymer substrate layer, and partial peeling of the conductive metal layer from the composite current collector, etc. The smaller the shedding rate of the conductive metal layer, the better the electrolyte resistance of the multilayer composite current collector. The shedding rate of the multilayer composite current collector of the present invention after the electrolyte immersion treatment is less than 2%, the interlayer adhesion is strong, and it is not easy to fall off or form burrs, etc., and it has excellent electrolyte resistance.
[0032] The present invention also provides a pole piece, comprising the multilayer composite current collector of the present invention. The pole piece can be prepared by a known method, for example, coating the electrode active material on the surface of the current collector of the present invention, drying, rolling, and cutting to form a pole piece. The electrode active material includes a positive electrode active material and a negative electrode active material. The positive electrode active material can be any one of a lithium cobalt oxide (LCO) system, a nickel cobalt manganese ternary (NCM) system, a nickel cobalt aluminum ternary (NCA) system, or a lithium iron phosphate (LFP) system. The negative electrode active material can be any one of a graphite system, a silicon carbon system, or metal lithium and its alloys. The coating thickness of the electrode active material is 10 microns to 100 microns. The drying conditions can be divided into three stages, for example, the first stage is dried at 80°C for 1min to 5min, the second stage is dried at 110°C for 1min to 5min, and the third stage is dried at 80°C for 1min to 5min. The roller compaction density can be controlled at 1.3 to 3.8 mg / cm 3 .
[0033] The present invention also provides a lithium ion battery comprising the pole piece of the present invention.
[0034] The lithium ion battery of the present invention can be used in consumer electronic products such as mobile phones and laptop computers, and can also be used in the fields of electric vehicles, electric vehicles, energy storage power stations, etc. The lithium battery of the present invention has the characteristics of high safety and high energy density. DETAILED DESCRIPTION
[0035] In order to make the purpose, structure and advantages of the present invention more clear and easy to understand, the present application is described in more detail through the following examples, but the test methods and materials used in the examples do not constitute a limitation of the present invention.
[0036] The test methods used in the embodiments and comparative examples of the present invention are as follows. For all tests, if the temperature during the test is not clearly defined, the tests are carried out in a laboratory at 20-25° C. and 50-60% RH.
[0037] Tensile strength of polymer substrate layer and composite current collector finished product:
[0038] The test was conducted using a universal tensile testing machine (AGS-X model produced by Shimadzu Corporation). The test standard can refer to ASTM-D882, and the sample was cut into 10mm wide × 150mm long strips in the MD direction and TD direction, with 5 strips cut in each direction. Test conditions: the initial distance between the upper and lower chucks was 100mm, the tensile speed was 200mm / min, and the arithmetic mean of the test results of the 5 strips was taken as the MD / TD tensile strength value of the sample.
[0039] Thickness of reinforcement layer and conductive metal layer:
[0040] The test was conducted using a transmission electron microscope (JEOL F200, manufactured by Japan Electronics). Three random locations of the sample were selected for embedding and curing with epoxy resin, and then the sample was pre-processed using the ultra-thin section pre-treatment method. The observation magnification was at least 100,000 times, and the thickness of the five different locations was observed and measured. The arithmetic mean of the five different locations was taken as the thickness of the layer.
[0041] Square resistance:
[0042] The current collectors of the embodiments and comparative examples were tested using a four-probe resistance tester (MCP-T610 model produced by Mitsubishi Chemical Corporation). The square resistance values of the test samples at 5 different positions were measured, and the arithmetic average of the 5 square resistance values was taken as the square resistance value of the sample.
[0043] Electrolyte immersion treatment:
[0044] Step 1) Cut the current collectors prepared in the examples and comparative examples into 10 cm×20 cm pieces as samples and place them in aluminum-plastic film bags.
[0045] Step 2) In an environment where the volume content of water and oxygen is less than 0.1ppm, the electrolyte is injected into the aluminum-plastic film bag containing the current collector in step 1), and it is necessary to ensure that the amount of the electrolyte is sufficient to immerse the internal current collector when it is laid flat, wherein the electrolyte comprises a lithium salt, a solvent, and an additive, wherein the lithium salt comprises one or more of lithium bis(trifluoromethylsulfonic acid)imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6) or lithium hexafluoroarsenate (LiAsF6), the solvent comprises one or more of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), and the additive is VC; the lithium salt used in this test is lithium hexafluorophosphate (LiPF6), the solvent is ethylene carbonate (EC), and the additive is VC.
[0046] Step 3) vacuum sealing the aluminum-plastic film bag containing the current collector and the electrolyte in step 2);
[0047] Step 4) placing the sealed aluminum-plastic film bag containing the current collector and the electrolyte in step 3) in an oven at 80° C. for 3 days before taking it out.
[0048] Step 5) In an environment where the volume content of water and oxygen is less than 0.1 ppm, the current collector sample treated in step 4) is taken out from the electrolyte, and is soaked and cleaned with diethyl carbonate solvent for 3 times. After drying, the shedding rate of the conductive metal layer is tested.
[0049] Conductive metal layer shedding rate test: tested before and after electrolyte treatment
[0050] The current collectors prepared in the embodiments and comparative examples were cut into strips with a width of 2.5 cm and a length of 18 cm. The current collectors prepared in the embodiments and comparative examples with a width of 2.5 cm and a length of 18 cm were taken and the following tests were performed respectively: the samples were cut into strips with a width of 2.5 cm and a length of 18 cm. The samples were tested with an adhesion of 350 g / cm 2 -400g / cm 2 The tape (3M610 tape or tape of equivalent effect) is attached to the conductive metal layer of the current collector. The bonding area is the same width as the tape (12cm). One end of the tape (end A) is fixed on the sample, and the other end (end B) is kept long enough not to be attached to the sample. When bonding, use a roller weighing 2kg to roll on the bonding area 3 times to make the tape and the conductive layer fit tightly. Use a VPA-2 high-speed stripping machine produced by KYOWA to fix the sample on the moving platform of the device, and the B end of the tape is fixed to the fixed end of the device. Then, the bonding area is peeled 180° at a speed of 20000mm / min, and the peeling length is set to 10cm. After the test, use a universal projector to observe whether there is any metal stuck to the contact surface of the tape and the metal layer peeled off from the current collector in the above experiment. If so, use a universal projector to measure the size of the metal shedding, based on the clear observation of the metal layer shedding area, and calculate the metal layer shedding rate by this size.
[0051] Metal layer peeling rate = ((metal area S1 before peeling test - metal layer area S2 after peeling test) / S1) × 100.
[0052] Battery yield:
[0053] The multilayer composite current collector of the present invention is used as the substrate, the positive electrode active material uses the lithium cobalt oxide (LCO) system, and the negative electrode active material uses the graphite system to manufacture the target 20 batteries. First, the electrode active material is coated on the surface of the current collector of the present invention, dried (dried at 80℃ and 110℃ for 1min to 5min respectively), and then rolled (the compaction density can be controlled at 1.3 to 3.8mg / cm 3), cut to form pole pieces. Then use the conventional battery manufacturing method to manufacture the battery, wherein at least one of the positive and negative electrodes includes the pole piece using the composite current collector. The goal is to manufacture 20 batteries, and count the number of batteries actually made, and the number of manufacturing failures and the reasons. Carry out the first charge and discharge experiment on the manufactured batteries to confirm whether they can be charged and discharged normally, and count the number of batteries that cannot be charged and discharged normally. The number of problems such as composite current collector breakage and penetration that occur in the above-mentioned electrode processing is added to the number of batteries that cannot be charged and discharged, and the proportion of this part to the target battery is the yield of the battery processing.
[0054] The materials used in the embodiments and comparative examples are as follows:
[0055] Polymer substrate layer:
[0056] 1) PET-1: Biaxially oriented polyethylene terephthalate film, produced by Toray's Korean factory XR40H, thickness 6 microns, tensile strength MD: 363MPa, TD: 265MPa, thermal shrinkage at 150℃×30min MD: 2.5%, TD: 0.6%.
[0057] 2) PET-2: biaxially oriented polyethylene terephthalate film, SPECIAL EFFICIENCY produced by Jiangsu Doublestar Color Plastic New Materials Co., Ltd., thickness 6 microns, tensile strength MD: 219MPa, TD: 268MPa, thermal shrinkage at 150℃×30min MD: 0.8%, TD: 1.2%.
[0058] 3) PPS: Biaxially oriented polyphenylene sulfide film, produced by Toray Industries, Ltd. 1X00, thickness 4 microns, tensile strength MD: 235MPa, TD: 204MPa, thermal shrinkage rate at 150℃×30min MD: 1.2%, TD: 0.4%.
[0059] 4) PP: biaxially oriented polypropylene film, 6D-2172 produced by Toray Industries, Ltd., thickness 6 μm, tensile strength MD: 181 MPa, TD: 362 MPa, thermal shrinkage at 140°C × 30 min MD: 4.3%, TD: 3.3%.
[0060] Adhesion enhancing layer:
[0061] 1) Polyurethane resin: Mitsui Chemicals TAKELAC WPB-341 model, Fourier transform infrared spectrometer can detect -1 The wavenumber range includes NH stretching vibration peak and 1539cm -1The wave number range includes the combined frequency peaks of NH bending vibration and CN stretching vibration, the coating thickness is 200nm, the drying conditions are: 120℃, 1 minute, and the aging conditions are: 23℃, 2 days.
[0062] 2) Modified polyolefin resins: Special olefin polymers, CHEMIPEARL HP400 produced by Mitsui Chemicals and TAKELAC produced by Mitsui Chemicals TM W-6355 polar film-forming aid, coating ratio: HP400 / W6355=80 / 20, Fourier transform infrared spectrometer can detect -1 The wavenumber range includes the asymmetric stretching vibration peaks of CH2 and CH3 at 2868 cm -1 The wavenumber range includes the symmetrical stretching vibration peaks of CH2 and CH3 at 1250 cm -1 The wave number range includes a CO stretching vibration peak, the coating thickness is 1000 nm, the drying method is UV irradiation, the UV irradiation conditions are: metal halide lamp 100W×3, line speed 10m / min, total irradiation energy 500mJ, and the drying conditions are: 60°C, 2 minutes.
[0063] 3) Alumina: Beijing Zhongnuo New Materials produces aluminum particles with a particle size of 3 to 4 mm.
[0064] 4) Metal nickel: Use metal nickel with a purity of 99.8%.
[0065] Conductive metal layer:
[0066] 1) Aluminum: Zhongnuo New Materials (Beijing) Co., Ltd., type 5N.
[0067] 2) Copper: Zhongnuo New Materials (Beijing) Co., Ltd., type 6N.
[0068] Embodiment 1, 2, 3, 5
[0069] According to the ingredients shown in Table 1, Examples 1, 2, 3, and 5 use a corona treatment machine to perform corona treatment on both sides of the substrate, and then the metals or metal oxides shown in Table 1 are simultaneously or successively deposited on both sides of the polymer substrate layer by vapor deposition to form a metal or metal oxide adhesion enhancing layer. Then, a vapor deposition machine (TEMD-500 produced by Beijing Techno Technology Co., Ltd.) is used to vapor-deposit a conductive metal layer with a purity of ≥99.8% on the surface of the adhesion enhancing layer to the target thickness of Table 1, thereby preparing a multi-layer composite current collector. The obtained samples were tested for various properties, and the results are listed in Table 1.
[0070] Embodiment 4, 6
[0071] According to the composition shown in Table 1, Examples 4 and 6 used a corona treatment machine to perform corona treatment on both sides of the substrate, and then coated the two sides of the corona treated substrate with the materials shown in Table 1, and then aged, and then used a vapor deposition machine (TEMD-500 produced by Beijing Techno Technology Co., Ltd.) to vapor-deposit a conductive metal layer with a purity of ≥99.8% on the surface of the coated substrate to the target thickness of Table 1. Subsequently, the other surface of the polymer substrate layer was also subjected to the same treatment as above to obtain a multi-layer composite current collector. The obtained samples were tested for various properties, and the results are listed in Table 1.
[0072] Embodiment 7, 8, 9
[0073] According to the components shown in Table 2, Examples 7, 8, and 9 used a corona treatment machine to perform corona treatment on both sides of the substrate, and then coated the adhesion enhancement layer on both sides of the corona treated substrate, and then aged (the coating materials are shown in Table 2), and then used a vapor deposition machine (TEMD-500 produced by Beijing Techno Technology Co., Ltd.) to vapor-deposit a conductive metal layer with a purity of ≥99.8% on the surface of the coated substrate to the target thickness of Table 2. Subsequently, the other surface of the polymer substrate layer was also subjected to the same treatment as above to obtain a multi-layer composite current collector. The obtained samples were tested for various properties, and the results are listed in Table 2.
[0074] Comparative Example 1
[0075] According to the composition shown in Table 1, in Comparative Example 1, a corona treatment machine was first used to perform corona treatment on both sides of the substrate, and then a vapor deposition machine (TEMD-500 produced by Beijing Techno Technology Co., Ltd.) was directly used to vapor-deposit a conductive metal layer with a purity of ≥99.8% to the target thickness of Table 1 on both sides of the corona treated substrate to prepare a multi-layer composite current collector. The obtained samples were tested for various properties, and the results are listed in Table 1.
[0076] Comparative Example 2
[0077] According to the composition shown in Table 1, in Comparative Example 2, the two sides of the substrate are first corona treated by a corona treatment machine, and then the aluminum oxide shown in Table 1 is simultaneously or successively deposited on both sides of the polymer substrate layer by vapor deposition to form an adhesion enhancement layer on both sides of the corona treated substrate. Then, a conductive metal layer with a purity of ≥99.8% is evaporated using a vapor deposition machine (TEMD-500 produced by Beijing Techno Technology Co., Ltd.) to the target thickness of Table 1 to prepare a multi-layer composite current collector. The obtained samples were tested for various properties, and the results are listed in Table 1.
[0078] Comparative Example 3
[0079] According to the composition shown in Table 2, in Comparative Example 3, a corona treatment machine was first used to perform corona treatment on both sides of the substrate, and then a conductive metal layer with a purity of ≥99.8% was evaporated on both sides of the corona treated substrate using a vapor deposition machine (TEMD-500 produced by Beijing Techno Technology Co., Ltd.) to the target thickness of Table 2, thereby preparing a multi-layer composite current collector. The obtained samples were tested for various properties, and the results obtained are listed in Table 2.
[0080] As shown in Table 1 below, according to the comparison between Example 2 and Comparative Example 1, it can be seen that the metal layer of the current collector without the adhesion enhancement layer is easy to fall off, and the falling area is larger after being immersed in the electrolyte.
[0081] According to the results of the current collector shedding rate of the adhesion enhancing layer of the same material with different thicknesses in Examples 1-3, it can be seen that the metal shedding rate can be made smaller by adjusting the thickness of the adhesion enhancing layer.
[0082] By comparing Examples 3 and 4, it can be seen that in the negative electrode current collector, the current collector with a polyolefin adhesion enhancing layer prepared by a coating method is more effective in improving the problem of metal layer shedding than the current collector with a nickel metal adhesion enhancing layer prepared by an evaporation coating method.
[0083] By comparing Examples 5 and 6, it can be seen that in the positive electrode current collector, the metal layer of the current collector containing the polyurethane adhesion enhancing layer prepared by the coating method is less detached than the current collector containing the aluminum oxide adhesion enhancing layer prepared by the evaporation coating method.
[0084] It can be seen from Comparative Example 2 that in the processing of the positive electrode current collector, the tensile strength of the current collector is low, which may easily cause problems such as tape breakage, affecting the yield rate of the entire battery processing process.
[0085] As shown in Table 2 below, according to the comparison between Examples 7, 8, and 9 and Comparative Example 3, it can be seen that for the composite current collector of the negative electrode, the current collector without an adhesion enhancing layer has a metal layer that is prone to falling off, and after being immersed in the electrolyte, the falling off area is larger; and as the metal falls off, the current collector loses the function of collecting positive and negative electrode electrons and serving as a conductive electron matrix, thereby affecting the overall yield of the battery.
[0086] According to the comparison between Examples 7, 8, and 9, it can be seen that the current collector with an adhesion enhancement layer has different electrolyte resistance performance with adhesion enhancement layers of different thicknesses. The metal shedding area after electrolyte immersion can be achieved in the optimal thickness; a small amount of metal will also fall off after electrolyte immersion for adhesion enhancement layers that are too thin or too thick, such as Examples 7 and 8, which will also affect the battery yield. The lower the metal layer shedding rate, the higher the battery yield.
[0087] Table 1
[0088]
[0089] Table 2
[0090]
Claims
1. A multilayer composite current collector, characterized in that: include: A polymer substrate layer, and a conductive metal layer arranged on both sides of the polymer substrate layer, wherein an adhesion enhancing layer is provided between the polymer substrate layer and the conductive metal layer, and the tensile strength of the composite current collector in the MD direction is above 150 MPa and in the TD direction is above 150 MPa.
2. The multilayer composite current collector according to claim 1, characterized in that: The adhesion enhancing layer is obtained by vapor deposition, evaporation coating or coating.
3. The multilayer composite current collector according to claim 2, characterized in that: The adhesion enhancing layer is obtained by vapor deposition or evaporation coating, and the material of the adhesion enhancing layer is a metal, metal oxide or alloy selected from copper alloy, metal nickel, nickel alloy, titanium, titanium alloy, aluminum oxide and aluminum alloy.
4. The multi-layer composite current collector according to claim 2, characterized in that: The adhesion enhancing layer is obtained by a coating method, and the material of the adhesion enhancing layer is selected from one or more of polyurethane resin, modified polyolefin resin, epoxy resin, unsaturated polyester resin, acrylic resin or fluororesin.
5. The multi-layer composite current collector according to claim 4, characterized in that: The adhesion enhancing layer contains one or more functional groups selected from -COOH, -Ar-OH, -OH, -Cl, -NHCO-, -NH2, -SH, -Si-OH, -CHO, -OC(=O)-O-, and -CO-O-.
6. The multi-layer composite current collector according to claim 1, characterized in that: The thickness of the adhesion enhancement layer is 10 nanometers to 1000 nanometers.
7. The multi-layer composite current collector according to claim 1, characterized in that: The thickness of the polymer substrate layer is 1 micrometer to 8 micrometers, and the thickness of the conductive metal layer is 0.5 micrometer to 2 micrometers.
8. The multi-layer composite current collector according to claim 1, characterized in that: The tensile strength of the polymer substrate layer of the composite current collector for the positive electrode is 250 MPa or more in the MD direction and 200 MPa or more in the TD direction. The tensile strength of the polymer substrate layer of the composite current collector for the negative electrode is 150 MPa or more in the MD direction and 200 MPa or more in the TD direction.
9. The multi-layer composite current collector according to claim 1, characterized in that: The material of the polymer substrate layer is one or more of polyester, polypropylene, polyimide, polyphenylene sulfide, polyamide, polyvinyl chloride, polyetheretherketone or polyether.
10. The multi-layer composite current collector according to claim 1, characterized in that: The conductive metal layer is prepared by at least one or more methods selected from the group consisting of vacuum sputtering, evaporation coating, chemical coating, metal foil lamination, electrochemical deposition, chemical vapor deposition, and physical vapor deposition.
11. The multi-layer composite current collector according to claim 1, characterized in that: The conductive metal layer may be made of one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver and silver alloy.
12. The multilayer composite current collector according to any one of claims 1 to 11, characterized in that: The sheet resistance of the multi-layer composite current collector is less than 50 milliohms.
13. The multi-layer composite current collector according to claim 1, characterized in that: After being immersed in electrolyte at 80° C. for 3 days, the shedding rate of the conductive metal layer is less than 2%.
14. A pole piece, characterized in that: A multi-layer composite current collector comprising any one of claims 1 to 13.
15. A lithium ion battery, characterized in that: A pole piece comprising the pole piece as claimed in claim 14.
Citation Information
Patent Citations
Preparation method of high energy density lithium ion battery
CN109088045A
Cathode current collector with composite structure and energy storage device
CN211957791U
Cited By
Multilayer current collector and preparation method and application thereof
CN120149423A
Composite copper current collector and preparation method and application thereof
CN120834213A